Bulk and grain boundary Li-diffusion in dense LiMn2O4 pellets by means of isotope exchange and ToF-SIMS analysis. Issue 47 (20th November 2019) - Schwab, C.; Höweling, A.; Windmüller, A.; Gonzalez-Julian, J.; Möller, S.; Binder, J. R.; Uhlenbruck, S.; Guillon, O.; Martin, M.
Abstract : Bulk and grain boundary diffusion of lithium in the cathode material LiMn2 O4 : experimental data and modeling. Abstract : Lithium diffusion in LiMn2 O4 pellets is studied by means of isotope exchange and Time-of-Flight Secondary Ion Mass Spectrometry (ToF-SIMS). A 6 Li-enriched film deposited by Pulsed Laser Deposition (PLD) on a dense LiMn2 O4 pellet with natural abundance of lithium isotopes is used to study the tracer diffusion of lithium. The measured profiles are analyzed by numerical models describing the 6 Li tracer diffusion from the film into the pellet. Experiments in the Harrison type B regime of diffusion kinetics allow for the distinction and simultaneous determination of bulk and grain boundary diffusion coefficients. Changing the experimental conditions to reach Harrison type A behavior yields effective diffusion coefficients for lithium tracer diffusion in LiMn2 O4 . Activation energies for bulk and grain boundary diffusion were obtained from experiments at different temperatures. Our values are critically compared to previous studies.